Preparation and Properties of Human Prothrombin Complex - Tishkoff, G. H; Williams, L. C; Brown, D. M (Thrombosis and Haemostasis, 1970)
As a corollary to our previous studies with bovine prothrombin, we have initiated a study of human prothrombin complex. This product has been isolated in crystalline form as a barium glycoprotein interaction product. Product yields were reduced compared to bovine product due to the increased solubility of the barium glycoprotein interaction product. On occasion the crystalline complex exhibited good yields. The specific activity of the crystalline complex was 1851 Iowa u/mg. Further purification of human prothrombin complex was made by removal of barium and by chromatography on Sephadex G-100 gels. The final product evidenced multiple procoagulant activities (II, VII, IX and X). The monomeric molecular weight determined by sedimentation equilibrium in a solvent of 6 M guanidine-HCl and 0.5% mercaptoethanol was 70,191 ± 3,057 and was homogeneous with respect to molecular weight. This product was characterized in regard to physical constants and chemical composition. In general, the molecular properties of human prothrombin complex are very similar to the comparable bovine product. In some preparations a reversible proteolytic enzyme inhibitor (p-aminophenylarsonic acid) was employed in the ultrafiltration step of the purification scheme to inhibit protein degradation.